Evaluation of the relationship between coronary artery disease complexity and metabolic and hormonal parameters in non-diabetic patients with acute coronary syndrome - Seker, Mehmet; Isik, Omer; Polat, Esra; Sabanoglu, Cengiz; Dagli, Mustafa Necati (Bmc, 2026)
Introduction Despite long-standing research on the relationship between coronary artery disease complexity and metabolic and hormonal parameters, the number of studies focusing on non-diabetic patients, a key subgroup of this disease, has remained limited. This study aims to investigate the relationship between specific metabolic and hormonal markers and disease complexity in non-diabetic patients with coronary artery disease. This work is intended to contribute to a growing body of literature, supporting the accelerating trend in research rather than the previously observed plateau. Materials and methods In this single-center observational study, between January 2021 and December 2024, patients hospitalized with acute coronary syndrome and undergoing coronary angiography were retrospectively screened based on their medical records and laboratory data (blood tests obtained after fasting for at least 12 hours). Patients were categorized into two groups: those with a diagnosis of diabetes and those without. A relationship analysis was performed between the two groups based on HbA1c levels (HbA1c >= 6.5% and HbA1c < 6.5%) and hospital Information Management System data, information on whether or not the patient has been previously diagnosed with diabetes.Additionally, an analysis of the SYNTAX score and its components was conducted to investigate the association between coronary artery disease complexity and various metabolic and hormonal parameters in non-diabetic patients with acute coronary syndrome by identifying correlations differing from those observed in the diabetic group. Results Among the 636 study participants, the mean HbA1c level was 6.34 +/- 1.38. Of these patients, 65.4% (n = 416) had HbA1c levels of 6.4% or below, while 34.6% (n = 220) had levels of 6.5% or above. Spearman correlation analysis was used to evaluate the relationships between non-normal distributions of the SYNTAX score and clinical and biochemical variables. The SYNTAX score demonstrated a positive and statistically significant correlation with HbA1c (r = 0.242, p < 0.05), age (rho = 0.215, p < 0.05), and serum uric acid (SUA) (rho = 0.139, p < 0.05). In the group with HbA1c levels < 6.5%, there was a positive correlation between the SYNTAX score and HbA1c, age, and serum uric acid. In contrast, in the group with HbA1c levels >= 6.5%, the SYNTAX score showed a positive correlation only with age (rho = 0.164, p < 0.05), and negative correlation with GGT (rho = -0.152, p < 0.05) and BMI (rho = -0.144, p < 0.05). Conclusion TSH and serum uric acid (SUA) levels were independently associated with the severity of coronary artery disease, particularly in the non-diabetic subgroup of patients with obstructive coronary artery disease. These findings may support more accurate risk stratification in clinical practice and facilitate the development of tailored approaches for each coronary artery disease subgroup by identifying potential new target parameters.
Keywords: Non-Diabetic; Coronary Artery Disease; Acute Coronary Syndrome; Syntax; Alevated Serum Uric Acid; Thyroid-Stimulating Hormone